MONITORING OF WATER QUALITY ON REARING INTENSIVE PONDS OF VANNAMEI SHRIMP (litopenaeus vannamei) IN CV. TIRTA MAKMUR ABADI LOMBANG - Ritonga, Lusiana BR (Universitas Tidar, 2023)
Vannamei shrimp (Litopenaeus vannamei) is a fishery commodity that has a very important value in the international market. Water quality monitoring is one of the key factors in the success of cultivation. Water quality plays an important role in determining the growth and survival of vaname shrimp. The parameters measured in this study were brightness, color, pH, DO, temperature, salinity, total alkali, TOM, ammonium, nitrite and phosphate. The purpose of this study was to determine the condition of the water quality in the vaname shrimp (Litopenaeus Vannamei) pond in CV. Tirta Makmur Abadi Lombang.